Towards Indonesia’s 2024 : an Analysis Presidential Campaign Advertisements - Ahmad, Entus Nuryana; Maha Rani, Ni Luh Ratih; Budiyanti, Elisa (Universitas Islam Negeri Raden Intan Lampung, 2023)
Social media has become a weapon to gain public sympathy in the 2024 presidential election. It cannot be denied that votes on social media have great potential for presidential and vice presidential candidates to gain popularity. Each pair of presidential candidates uses many ways to carry out political communication, one of which is via YouTube. Every message created by each potential leader certainly has meaning. Some symbols and signs contain messages from the presidential and vice presidential candidates. This message usually describes the candidate's image according to their character and the vision and mission they want to build. This research aims to analyze the signs in the political advertisements of Anis-Imin, Prabowo-Gibran, and Ganjar-Mahfud. This qualitative research uses semiotic analysis. The objects in this research are advertisements for the three Indonesian presidential and vice presidential candidates in 2024. The advertisements for the three presidential and vice presidential candidates have their characteristics. The other signs that appear in the three advertisements have similarities and differences. Advertisements for presidential and vice presidential candidates number 1 and 2 are more comprehensive in discussing various issues. Meanwhile, the ad for presidential candidate vice presidential candidate number 3 tends to be packaged more simply.